2023
DOI: 10.52004/jemca2022.0006
|View full text |Cite
|
Sign up to set email alerts
|

Passive surveillance records including nuisance or suspected invasive/non-native mosquitoes in the United Kingdom, 2005-2021

Abstract: Alongside active surveillance at ports and land transport sites, the UK Health Security Agency runs a passive mosquito surveillance scheme: The Mosquito Recording Scheme (MRS). The MRS is a citizen-science scheme, it receives and identifies mosquitoes submitted by members of the public, including in response to nuisance biting incidents. The aims of the scheme are to detect unusual or invasive species, provide a log of reportable incidents of nuisance mosquito biting, and gain insight into the seasonality of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Surveys then proceeded northward and were conducted nearby at Mersea Island and Wivenhoe and despite reports of nuisance biting at Wivenhoe submitted with an adult Cx. modestus to the MEZE's Mosquito Recording Scheme in June 2018 (Johnston et al, 2023), no larvae were found at either location. The species was recorded in ditches at Horsey Island, but not at ditches at nearby Walton Hall Marshes.…”
Section: Distribution Of Culex Modestusmentioning
confidence: 94%
See 1 more Smart Citation
“…Surveys then proceeded northward and were conducted nearby at Mersea Island and Wivenhoe and despite reports of nuisance biting at Wivenhoe submitted with an adult Cx. modestus to the MEZE's Mosquito Recording Scheme in June 2018 (Johnston et al, 2023), no larvae were found at either location. The species was recorded in ditches at Horsey Island, but not at ditches at nearby Walton Hall Marshes.…”
Section: Distribution Of Culex Modestusmentioning
confidence: 94%
“…Medlock and A. Vaux, unpublished data). There have been no reported human cases of locally acquired mosquito-borne disease in Britain in the last decades (Johnston et al, 2023;Medlock et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is the northernmost mosquito record of Great Britain to date, while the second northernmost is a recent (19/09/2021) citizen report of Cs. annulata found on Fair Isle, Shetland (Johnston et al, 2023) (Figure 1). Species 1886-1900 1901-1925 1926-1950 1951-1975 1976-2000 2001-2020 Aedes annulipes.…”
Section: New Data Collected Through Field Sampling In England and Sco...mentioning
confidence: 99%
“…published and grey literature, citizen science data) are gathered under the Mosquito Recording Scheme (MRS) run by the UK Health Security Agency. The MRS also gathers citizen-science data, receiving and identifying mosquitoes submitted by members of the public, including data that is associated with nuisance biting incidents (Johnston et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Testing new formulations of insect growth regulators, the only authorised alternative to microbial insecticide for mosquito larviciding, is very helpful, even when their field application is conditioned by the larval environment (for not impacting non-target organisms) and by the national regulations. There are many methods for surveying and monitoring mosquito species and the three articles in this issue illustrate well the spectrum, with a snapshot field survey performed in the British Caribbean islands of Turks and Caicos (Medlock et al, 2023), a three-year analysis of the nuisance-causing mosquito fauna in a Swedish municipality (Hesson et al, 2023), and a passive surveillance scheme of native and nonnative mosquito species in the United Kingdom (Johnston et al, 2023).…”
mentioning
confidence: 99%